ORGANISASI KEMASYARAKATAN PERSPEKTIF HAK ASASI MANUSIA - Hartono Hartono (Islamic Family Law, STAI Sangatta Kutai Timur, 2023)
The rights to associate and assemble that are indebted to social organizations are citizens' rights that are protected by the Indonesian constitution. In the course of history, the Indonesian nation cannot be separated from the presence of these social organizations. The theoretical framework used in viewing the problem above as an analytical tool includes human rights theory. While the method in writing this journal is doctrinal research with a qualitative approach in the form of a prescriptive law as its object. Sources of data are in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of this study indicate that; the right to associate and assemble in the form of community organizations for citizens is constitutionally protected. However, the rights to associate and group are derogable rights, namely rights that the state may reduce or limit when these rights threaten the rights of other people.